Consequences of COVID-19 for geriatric patients during a pandemic - Ludwig Wemhöner; Charlotte Brandts; Hannah Dinse; Eva-Maria Skoda; Sarah Jansen; Martin Teufel; Hana Rohn; Richard Dodel (Scientific Reports)
Abstract To investigate the outcomes of geriatric COVID-19 patients in a German academic setting during the pandemic. This study included 468 consecutive geriatric patients (≥ 70 years) who tested positive for SARS-CoV-2 and were treated at the University of Duisburg-Essen from 2/2020 to 3/2021. 74 patients were transferred to a geriatric hospital and a 12-month follow-up (prospective study) was performed in 51 patients. Clinical assessments evaluated depression (GDS), apathy (AES), cognitive status (MMST), mobility (TUG), health status (EQ-5D-5 L), and daily living activities (Barthel Index). Demographic and clinical data were also analyzed. Results showed that the mortality in this vulnerable group was 52% (n = 209). Long-term survival was higher in patients who received comprehensive geriatric treatment (74.3% vs. 51.8%). The duration of inpatient stay at the primary hospital was 13.3 ± 3.6 days, with 28.8% (n = 135) requiring intensive care. At the 12-month mark more patients with geriatric treatment lived in nursing homes. Barthel-Index/Timed-Up-and-Go-Test/MMST/AES/GDS, and EQ-5D-5 L indicated worse outcomes in the group who received geriatric treatment. Specialized geriatric care may improve survival in geriatric COVID-19 patients despite decreased long-term outcomes. Further research, including international studies like NAPKON, are encouraged to confirm these findings and explore potential interventions for improved outcomes in this vulnerable population.